Cooperative Learning Model Make a Match Type Assistance in Crossword Puzzle Games Improves Citizenship Learning Outcomes - Risdiyanto Prayoga; Mukhamad Murdiono; Obby Taufik Hidayat (Universitas Pendidikan Ganesha, 2023)
Fun learning and engaging students in the learning process are the main learning goals, with a fun and energetic class atmosphere. Students are still found to feel bored and passive in participating in learning; this problem ultimately impacts poor student learning outcomes. This study aims to analyze the cooperative learning model of the make-a-match type assisted by crossword puzzles on student learning outcomes in Civics subjects. The type of approach in this research is quasi-experimental design. The research subjects totaled 28 students. The research sample was taken by using a random sampling technique. The methods used are observation, interviews, tests, questionnaires, and documentation. The instrument used is the test. Data analysis technique using t-test. Data analysis showed that the make-a-match model assisted by crossword puzzles significantly affected student learning outcomes; there were differences before and after the action was given. It was concluded that there was an effect of the make-a-match model assisted by crosswords to improve student learning outcomes in Civics subjects. With the help of crosswords, the make-a-match model can make the class atmosphere active and fun.